2019
DOI: 10.3390/su11030860
|View full text |Cite
|
Sign up to set email alerts
|

Structural Impacts on Formation of Self-Efficacy and Its Performance Effects

Abstract: The role of organizational structure as an important contextual variable has long been recognized in affecting a host of employee attitudes and behaviors, but there is a dearth of theoretical and empirical research that examines the ways in which organizational structure influences the occurrence of self-efficacy and its performance effects. This study addresses this gap by exploring how the two core structural components—formalization and centralization—separately and jointly affect employee self-efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 136 publications
3
9
0
2
Order By: Relevance
“…This nding is consistent with Hultell, Melin, and Gustavsson's 2013 work, which indicated that decreases in TSE were associated with teachers' burnout levels. That is, high TSE re ects low-level burnout, while low TSE re ect high-level burnout (Skaalvik & Skaalvik, 2007, 2019. The ndings are also consistent with Avanzi et al (2012), who stated that there was a negative correlation between Italian teachers' e cacy student-and work-related burnout.…”
Section: Discussionsupporting
confidence: 74%
“…This nding is consistent with Hultell, Melin, and Gustavsson's 2013 work, which indicated that decreases in TSE were associated with teachers' burnout levels. That is, high TSE re ects low-level burnout, while low TSE re ect high-level burnout (Skaalvik & Skaalvik, 2007, 2019. The ndings are also consistent with Avanzi et al (2012), who stated that there was a negative correlation between Italian teachers' e cacy student-and work-related burnout.…”
Section: Discussionsupporting
confidence: 74%
“…The findings implied that most state corporations had some degree of bureaucracy mainly attributed to official code of conduct, well defined communication channels, hierarchical authority echelons and authorization red tapes thus limiting productivity and performance. The findings compare with Mustafa, Glavee-Geo, Gronhaug and Saber Almazrouei who studied the organizational structural impacts on formation of self-efficacy and its performance effects [34]. The study noted that self-efficacy and performance relationship is diminished under conditions of high formalization and high centralization.…”
Section: Degree Of Bureaucracysupporting
confidence: 56%
“…To gather the information required, the target population comprised all the 189 state corporations in Kenya (SCAC, 2019). These state corporations are subdivided into five categories which include: Commercial state corporations (34); commercial state corporations with strategic functions (21); executive agencies (62); independent regulatory agencies (25); and research institutions, public universities, tertiary education and training institutions (46).…”
Section: Target Populationmentioning
confidence: 99%
“…Hal tersebut tercipta karena nilai efikasi diri yang telah tertransformasi dalam diri semua warga sekolah khususnya tenaga pendidik dan kependidikan. Hal tersebut diperkuat dengan sebuah hasil studi yang menyatakan bahwa terbangunnya efikasi diri pada para pegawai di sebuah lembaga atau organisasi berdampak positif terhadap peningkatan kinerja (Mustafa, et. al., 2019) dan motivasi berprestasi (Cherian & Jacob, 2013).…”
Section: Efektifitas Kinerja Tenaga Pendidik Dan Kependidikanunclassified